Impact of Television Exposure on Aggressive Behavior Among Preschool Children - Gilang Ramadhan; S. Tauriana; Yuana Dwi Agustin (Genius Journal of Nursing, 2025)
Introduction: Television is a form of mass media that can influence children’s behavior, particularly through the internalization of social values presented in various programs. Excessive exposure to television content may contribute to the development of aggressive behavior in preschool children.Objectives: This study aimed to analyze the influence of television viewing on aggressive behavior among preschool children.Methods: This study employed an analytic correlational design with a cross-sectional approach. The sample consisted of 130 preschool children selected using a total sampling technique. Data were collected using structured questionnaires and analyzed using Spearman’s rho correlation test with a significance level of p < 0.05.Results: The results showed a statistically significant relationship between television viewing and aggressive behavior among preschool children (p = 0.008). The correlation coefficient (r = 0.439) indicated a moderate positive relationship, suggesting that higher exposure to television is associated with increased aggressive behavior.Conclusions: Television viewing has a significant influence on aggressive behavior among preschool children. These findings highlight the importance of parental supervision and guidance in managing children’s media exposure to prevent the development of aggressive behavior.